Pyaneti: a fast and powerful software suite for multiplanet radial velocity and transit fitting. Issue 1 (10th September 2018) - Barragán, O; Gandolfi, D; Antoniciello, G
ABSTRACT: Transiting exoplanet parameter estimation from time-series photometry and Doppler spectroscopy is fundamental to study planets' internal structures and compositions. Here we present the code pyaneti, a powerful and user-friendly software suite to perform multiplanet radial velocity and transit data fitting. The code uses a Bayesian approach combined with a Markov chain Monte Carlo sampling to estimate the parameters of planetary systems. We combine the numerical efficiency of fortran, the versatility of python, and the parallelization of OpenMP to make pyaneti a fast and easy to use code. The package is freely available at https://github.com/oscaribv/pyaneti .